Pelaksanaan Pembelajaran Daring Mata Pelajaran Bahasda Indonesia - Huteri Dea Agustina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the following things. First, to describe the presentation of online learning at SMP N Kota Sawahlunto? Second, to describe the interaction of online learning at SMP N Kota Sawahlunto? Third, to describe the evaluation of online learning at SMP N Kota Sawahlunto?. This type of research is a qualitative research using descriptive method. Qualitative data in this study is complemented by quantitative data. Qualitative data will be obtained from observation, interview, and documentation techniques. Meanwhile, quantitative data will be obtained from the results of the questionnaire. The sources of data in this study were four Indonesian language teachers and 80 grade VIII students of Sawahlunto City State Junior High School. The instrument in this study was the researcher himself for qualitative data and for the quantitative data instrument was a questionnaire. Data is analyzed by describing, analyzing, and discussing data based on theory. The theory used is the theory of online learning in Indonesian language learning. The research results are as follows. First, the implementation of online learning of Indonesian language subjects at SMP N Sawahlunto City can be said to be good if viewed from the perspective of online learning, teachers of Indonesian subjects at SMP Negeri Sawahlunto City have shown their efforts related to aspects of online learning presentations, online learning interactions, and evaluation of learning online.